Spray Coated Cellulose Nanofiber Laminates on the Paper to Enhance its Barrier and Mechanical Properties - Shanmugam, Kirubanandan (Journal of Sustainability and Environmental Management, 2022)
Cellulose nanofiber (CNF) is a sustainable biomaterial to replace the synthetic plastics for coating on the paper to enhance their barrier and mechanical properties. Spraying CNF is a flexible process for fabricating barrier layers on the paper. Spraying CNF suspension vary from 0.5 wt.% to 1.5 wt.% on the paper substrates gives coat weight varied from 2.9±0.7 to 29.3±6.9 g/m2. As a result, CNF coat weights act as barrier layers and reduced the air permeance from 0.78±0.17 to < 0.003 μm/Pa.S. Sprayed CNF fills the surface pores in the paper and formed barrier layers as laminates on the paper evaluated via SEM. Coated CNF also increase the mechanical strength of the paper from 109.7±7 to 131.1±13.4 N while tailoring the coat weight vary from 2.9±0.7 to 29.3±6.9 g/m2. This process can be implemented in a roll to roll coating with an integration of sprayer for continuous process via scale up.DOI: https://doi.org/10.5281/zenodo.6206013